KIPRAH GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBINA KARAKTER TANGGUNG JAWAB SOSIAL SISWA MADRASAH IBTIDAIYAH NEGERI 1 KARAWANG MASA PANDEMI COVID 19 - Saepul Pajri; Ibnu Muthi; Asep Dudin Abdul Latip (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
This thesis discussed the gait of Islamic Religious Education teachers in fostering the character of social responsibility. This character development aimed to make students of Madrasah (School) Ibtidaiyah Negeri 1 Karawang gain a sense of social responsibility. Also, it aimed to make the students be accustomed to applying these characters in daily interactions where students are. This research was motivated by the low social attitudes of students during the Covid-19 pandemic, especially the character of responsibility both to the personal and the environment. This problem made the author conducted research at Madarasa Ibtidaiyah Negeri 1 Karawang. This school seeks to make Islamic teachings the basis for implementing various characters, especially the character of social responsibility through various programs in the school. This research used a qualitative descriptive method. The object of the research was the Head of Madrasah, Deputy Head of Curriculum Sector, Deputy Head of Student Affairs, Islamic Religious Education Teachers, and Students. The data collection was conducted by observation, interviews, and documentation. The data were analyzed using triangulation techniques, data sources, and research extension. The results of the research showed Islamic Religious Education Teachers carry out a role in fostering the character of students social responsibility, like educating through and example, habits, advice and stories, discipline, participation, and nurturing. The use of existing methods and media was also maximized. In every step taken, there were factors that supported the implementation of a program and on the other hand, there were also inhibiting factors. In this case, how do we respond to it? These factors were: technological advancement factors, religious activities, living environment, friends, parents, and students. The author advised Madrasah should continue to familiarize and develop its programs, as well as support the development of social responsibility characters and students. The purpose is to make students obey the teachers and Madrasah rules to create a conducive learning atmosphere. Parents should be aware that in building the character of social responsibility, it is necessary to intervene from parents when students are at home. With a synergistic relationship between various parties, the objectives of the Madrasah can be achieved.